Contemporary external political landmarks of Ukraine: between the American scylla and the Russian charybdis - Serhiy Pron’ (Американська історія і політика, 2017)
The article analyzes the possible directions of the current foreign policy of Ukraine. The need to use both positive and negative experiences exemplified by the US, Scandinavian countries, Turkey, Singapore, Britain etc. have been underlined. For Ukraine, there is not and there shall be no future other than the European integration, but this does not mean that Ukraine should throw away the experience of reformation, stabilization and prosperity of Asian countries.